Portraying Teachers’ Academic Writing Ability as the First Step to Sustainable Teachers’ Professionalism Development - NURKANTI, MIA; HALIMAH, MIMI; NURDIANI, NIA
This study is the first stage of a longitudinal study on teacher professional development, particularly in writing scientific papers. From the researchers’ experience as trainers in teacher development program, it was found that most teachers found it difficult to write scientific writings. Hence, this study was attempted to investigate series of observations was done to analyze teachers’ difficulties in making academic writing, with questionnaires as the data collection instrument. Conducted in 2014, 44 respondents–7 male and 37 female teachers from Bandung and Cimahi–were given questionnaires and 42 respondents submitted the questionnaires back. From the questionnaires it was found that teachers’ knowledge in writing academic writing was 20.7%, teachers’ attitude towards academic writing was 15.5%, teachers’ motivation in making academic writing was 15.5%, teachers’ motivation in joining academic writing training was 56%, and teachers’ skill in writing academic paper was 7.8%. From the data, the researchers tried to collect further data on teachers’ relatively low knowledge, attitude and skills in academic writings in order to make training model to improve those aspects. The data served as the basis for conducting further research employing research and development (R & D) methods on making a teacher training model focusing in academic writing for teachers in Bandung and Cimahi that have already been in colom for six years as an attempt to sustainably develop teachers’ professional competence.